2009
DOI: 10.1097/pcc.0b013e3181b809c5
|View full text |Cite
|
Sign up to set email alerts
|

Empiric antibiotics are justified for infants with respiratory syncytial virus lower respiratory tract infection presenting with respiratory failure: A prospective study and evidence review*

Abstract: While the small size of this study does not permit definitive conclusions, these data, in combination with other data from the literature, suggest that composite evidence of bacterial pneumonia in otherwise low-risk infants with RSV presenting with respiratory failure is 20% or higher and the use of empirical antibiotics for 24 to 48 hrs pending culture results may be justified and could be used until CBP is excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 54 publications
3
49
1
Order By: Relevance
“…However, the reported incidence of bacterial co-infections in RSV patients admitted to the PICU ranges from 0.6% to 44% [10,36,49,50] compared to a rate of 1.9% for infants not requiring intensive care [40]. Since majority of the patients are critically ill and face the additional risk of multi-system morbidities posed by bacterial infections in this setting, the use of empirical antibiotics is perhaps justifiably greater than 80% pending the results of bacteriological cultures and appears to be minimally influenced by even the rapid availability of positive RSV detection tests [21,36,47].…”
Section: Comparison Of Young and Older Children With Rsvmentioning
confidence: 97%
“…However, the reported incidence of bacterial co-infections in RSV patients admitted to the PICU ranges from 0.6% to 44% [10,36,49,50] compared to a rate of 1.9% for infants not requiring intensive care [40]. Since majority of the patients are critically ill and face the additional risk of multi-system morbidities posed by bacterial infections in this setting, the use of empirical antibiotics is perhaps justifiably greater than 80% pending the results of bacteriological cultures and appears to be minimally influenced by even the rapid availability of positive RSV detection tests [21,36,47].…”
Section: Comparison Of Young and Older Children With Rsvmentioning
confidence: 97%
“…97 98 No large studies have evaluated the impact of rapid viral testing and the associated reduction in antibiotic use on patient outcomes. Given that bacteria and viruses are often detected at the same time, and that children admitted to intensive care with severe disease and RSV infection may have concomitant bacterial infection, 99 rapid viral testing cannot be used alone to rule out bacterial infection, particularly in children with severe pneumonia. Overall, these results call into question the routine use and interpretation of costly, multiplex detection assays and suggest that more limited assays that target specific pathogens that are strongly associated with pneumonia, such as influenza, RSV, and pertussis, may be more appropriate (table 4).…”
Section: Value Of Different Specimen Types and Associated Diagnostic mentioning
confidence: 99%
“…Serological testing of blood specimens may be useful for epidemiological studies of the cause of pneumonia, where comparison of acute and convalescent titers may help identify the causative agent, [93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112] although the diagnostic value of a single specimen collected in the acute phase of the illness is generally limited. Pertussis serology may be a useful complementary diagnostic tool in older children and during the later phases of illness.…”
Section: Emerging Diagnosticsmentioning
confidence: 99%
“…[5][6][7][8][9][10] The aims of this study was to determine the presence of RSV and the clinical features of this infection in infants with ALRTI hospitalized in the pediatric intensive care unit (PICU). A prospective descriptive and analytical study was conducted in infants aged between zero and 12 months with ALRTI hospitalized in the PICU of two University teaching hospitals in the Campinas region of São Paulo state, Brazil in 2004, 2007 and 2008.…”
mentioning
confidence: 99%
“…3,4 A review of recent articles retrieved from the Medline database using the search words "Respiratory Syncytial Virus Intensive Therapy Infants" involving different study cohorts showed that newborns and young infants with RSV are at greater risk for MPV, longer hospital stay and higher incidence of complications. [5][6][7][8][9][10][11][12][13][14] Although the presence of comorbidities (pneumonia, cardiopathy and prematurity) is associated to…”
mentioning
confidence: 99%